Electromagnetic shielding using ceramic materials - Kumari P.; Tripathi P.; Singh S.P.; Kumar D. (My University, 2025)
Traditional metal-, carbon- and polymer-based composites possess good electromagnetic interference (EMI) shielding characteristics, but they are weaker in mechanical strength and thermal stability. The control of EMI depends upon the degree of shielding required, the frequency range, the characteristics of the instrument that has to be shielded, and the processing as well as fabrication cost of EMI shielding materials. Ceramic materials have such properties as high strength, excellent wear resistance, antistatic, high fracture toughness, and high thermal as well as chemical stability. However, most of these materials do not possess good microwave-shielding behavior. Therefore, forming ceramic composites using a ceramic matrix phase and a conductive or EMI shielding material filler can guarantee good shielding characteristics even in harsh environments. In the recent decades, a variety of carbon nanomaterials, such as graphene, single- and multiwalled carbon nanotubes, and carbon fibers, have been widely investigated for their usage as EMI shields. EM-shielding and/or absorbing properties of various ceramic composites, such as graphene-ceramics, SiCN-based ceramic matrix composites, and ferrites, are described. Some special ceramics such as MXene ceramics, metal-organic frameworks, and sulfide ceramics show excellent EMI shielding behavior. This chapter deals with such ceramic materials, their properties, and potential applications. © 2020 Elsevier Inc. All rights reserved.